GREEN ENTREPRENEURSHIP DEVELOPMENT STRATEGY THROUGH SACK RECYCLING BUSINESS - Raden Putri Shafira Nur Chandra; Ridlwan Muttaqin (RADJA PUBLIKA, 2025)
This study aims to analyze the strategy for developing green entrepreneurship through the sack recycling business at the Abadi DMA Depot. The research method used is a qualitative descriptive approach with SWOT analysis and Business Model Canvas (BMC) tools. SWOT analysis is used to determine the strengths, weaknesses, opportunities, and threats faced by the Abadi DMA Depot. Meanwhile, the Business Model Canvas helps in defining the main components of the business that must be improved in order to achieve sustainable growth. The results of the study indicate that the sack recycling business has good potential for development, supported by the availability of raw materials, production cost efficiency, and increasing public awareness of environmentally friendly products. However, this business also faces several obstacles, such as limited capital and a fairly high level of market competition. The results of the Business Model Canvas analysis indicate that the sack recycling business has a value proposition in the form of environmental benefits and economic value, so it is worthy of being developed as a green entrepreneurship with management and finance.